Comparison between resource reservation protocol and next steps in signalling in mobile IP networks. Issue 2 (1st March 2015) - Mirzamany, Esmat; Lasebae, Aboubaker; Gemikonakli, Orhan
Abstract : Providing an acceptable level of quality of service (QoS) for critical applications is one of the interesting topics in next generation wireless networks. Confronting the major criticisms of resource reservation protocol (RSVP), the next steps in signalling (NSIS) was introduced as a general framework to include not only the RSVP but other signalling services in IP‐based networks. It attempts to address the RSVP shortcomings and to offer additional features. It is widely believed that NSIS can be considered as a suitable alternative for RSVP. However, it worsens the scalability issue in the RSVP operation, inherits the RSVP problem in mobile environments and its appealing features come with a significant cost. This study develops an analytical framework to evaluate the RSVP and NSIS performances in proxy mobile IPv6 (PMIPv6) environment. The results obtained showed a significant increase in network signalling cost, more bandwidth consumption by resource reservation signalling messages and a high resource re‐establishment latency in NSIS operations. The authors believe these outcomes raise doubts over the NSIS eligibility as a suitable replacement for RSVP.